Entomological surveillance in Caribbean wetlands of Colombia reveals Madariaga virus Lineage III in mosquito populations - Richard Onalbi Hoyos-López; María Claudia Atencia-Pineda; Salim Mattar (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Objectives Madariaga virus (MADV) is an emerging arboviral pathogen in Central and South America, but systematic entomological surveillance data remain limited in Colombia. We investigated MADV circulation in mosquitoes from the Alto Cotocá wetlands, Córdoba department, Colombia. Methods Adult mosquitoes were collected during November-December 2017 and February-March 2018 using CDC light traps, Shannon traps, and manual aspiration. A total of 2984 mosquitoes were processed in 136 pools of 1-20 specimens and screened using generic Alphavirus RT-PCR with MADV-specific confirmation, bidirectional sequencing, and Bayesian phylogenetic analysis. Results MADV was detected in 8 of 136 pools (5.9%) across five mosquito taxa: Culex erraticus, Culex quinquefasciatus, Culex spp., Mansonia titillans, and Psorophora ferox. The overall minimum infection rate was 2.68 per 1000 specimens (95% CI: 1.16-5.28). All sequences (GenBank MK131010-MK131017) clustered within Lineage III with 96.59%-96.62% identity to Colombian equine reference strains. Two haplotypes were identified among positive pools. Conclusion This baseline assessment provides molecular evidence of MADV Lineage III in Colombian mosquito populations, establishes methodology for expanded surveillance, and supports the inclusion of MADV in differential diagnostic and surveillance considerations for arboviral encephalitis in Colombia.